Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Teorema Pythagoras Spesifik Kebudayaan Adat Melayu Kepulauan Riau - Simanjuntak, Friska Yanti; Asmaul Husna; Nailul Himmi Hasibuan (STAI Al-Bahjah, 2025)
This research aims to determine and analyze the mathematical concept comprehension abilities of eighth-grade junior high school students on the topic of the Pythagorean Theorem, as well as to foster a sense of nationalism among students towards the Malay cultural heritage of the Riau Archipelago. The method applied in this research is descriptive qualitative. The subjects of this study are 30 eighth-grade students from SMP Negeri 3 Batam in the 2024/2025 academic year. The test instrument used in this research consists of 3 essay questions on the Pythagorean Theorem material specific to the Malay cultural customs of the Riau Archipelago. The keywords in this article are